Strengthening Inclusive Governance: Collaborative and Digital Pathways to People with Disability in Bali’s Tourism Sector - Siti Widharetno Mursalim; Anwar, Saekul; Nugraha , Muhammad Firman a (Department of Public Administration, Muhammadiyah University of Makassar, 2026)
Employment opportunities for persons with disabilities (PWDs) in Bali’s tourism sector remain limited despite the existence of supportive regulations, indicating a persistent gap between policy commitments and implementation. While previous studies have primarily focused on descriptive barriers, limited attention has been given to how governance mechanisms shape employment inclusion outcomes. This study applies an inclusive governance framework, operationalized through three dimensions-transparency, participation, and equality—to examine how governance mechanisms influence employment inclusion. Using a descriptive qualitative approach and the Miles and Huberman analytical model, data were collected through in-depth interviews, observations, and document analysis involving government institutions, NGOs, and PWDs. The findings reveal a persistent policy–practice gap driven by weak regulatory enforcement, fragmented information systems, and entrenched workplace stigma. Two key empirical insights emerge. First, digital employment platforms, particularly DNetwork, enhance transparency and improve job matching, thereby expanding access to employment opportunities for PWDs. Second, collaborative governance among government agencies, NGOs such as PUSPADI Bali, and the private sector contributes to increased employment inclusion, although its sustainability remains constrained by limited integration and resources. This study contributes to governance and public administration literature by demonstrating how digital integration and multi-stakeholder collaboration function as causal mechanisms that enable inclusive governance in practice. These results demonstrate that inclusive governance becomes effective when regulatory enforcement, digital integration, and multi-stakeholder collaboration are aligned, offering broader implications for inclusive labor policy in developing-country contexts.